2019
DOI: 10.21608/jappmu.2019.76532
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Phenotypic Parameters and Trends for Milk Yield, Service Period and Calving Interval and The Economic Impact of Extending A Calving Interval on-Farm Profitability in Friesian Cows in Egypt

Abstract: Genetic parameters for Friesian cows were estimated from 9155 lactation records for 3635 cows sired by 184 bulls. Multi-trait repeated animal models were employed using the REML procedure to estimate covariance components of total milk yield (TMY), service period (SP) and calving interval (CI). There is sufficient genetic variation (indicated by the coefficient of genetic variation) in total milk yield, service period and calving interval traits (15.6, 3.6 and 3.7%, respectively). Estimates of heritability for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 24 publications
5
4
1
Order By: Relevance
“…The TMY average of the present study (5778.15 kg) was higher (4227 kg) reported by Abosaq et al (2017), 2939 kg by Shehab El-Din (2020), and 3879 kg by Badr and Amer (2020), while it was lower than the TMY values of 8315 kg stated by Salem and Hammoud (2016), 6173.5 kg by Farrag et al (2017) and 8675 Overall mean of DO (99.56 d) detected in present study was shorter than means detected in different commercial Friesian herds (113.1, 144.49, 174.4, 166.50 and 159 d) obtained by (Salem and Hammoud, 2016;Abosaq et al, 2017;Farrag et al, 2017, Habib et al, 2020and Zahed et al, 2020. Also, the present mean of CI (377.4 d) was shorter than that of 414.43, 472.0, 433.2 and 427.72 days as presented by Abosaq et al (2017), Farrag et al (2017), Zahed et al (2019) and Habib et al (2020), respectively. Mean of NSC (1.99) was comparable to that values given by Salem and Hammoud (2016)(2.0), Sanad and Hassanane (2017)(1.93) and Abosaq et al (2017)(2.16), while it was lower than the values estimated by Habib et al (2020)(3.0) and Zahed et al (2020)(3.1).…”
Section: Resultssupporting
confidence: 40%
See 3 more Smart Citations
“…The TMY average of the present study (5778.15 kg) was higher (4227 kg) reported by Abosaq et al (2017), 2939 kg by Shehab El-Din (2020), and 3879 kg by Badr and Amer (2020), while it was lower than the TMY values of 8315 kg stated by Salem and Hammoud (2016), 6173.5 kg by Farrag et al (2017) and 8675 Overall mean of DO (99.56 d) detected in present study was shorter than means detected in different commercial Friesian herds (113.1, 144.49, 174.4, 166.50 and 159 d) obtained by (Salem and Hammoud, 2016;Abosaq et al, 2017;Farrag et al, 2017, Habib et al, 2020and Zahed et al, 2020. Also, the present mean of CI (377.4 d) was shorter than that of 414.43, 472.0, 433.2 and 427.72 days as presented by Abosaq et al (2017), Farrag et al (2017), Zahed et al (2019) and Habib et al (2020), respectively. Mean of NSC (1.99) was comparable to that values given by Salem and Hammoud (2016)(2.0), Sanad and Hassanane (2017)(1.93) and Abosaq et al (2017)(2.16), while it was lower than the values estimated by Habib et al (2020)(3.0) and Zahed et al (2020)(3.1).…”
Section: Resultssupporting
confidence: 40%
“…The heritability estimated for DO in present study (0.100) was in more close to the values of 0.105, 0.11 and 0.19 that recorded by Faid-Allah (2015), Rushdi (2015) and Habib et al (2020), while was higher than those estimated by Salem and Hammoud (2016), Abosaq et al (2017) and Zahed et al (2020) as being 0.028, 0.04 and 0.044, respectively. The CI heritability estimated (0.103) was higher than those noticed by Sanad (2016), Abosaq et al (2017), Zahed et al (2019) and Habib et al (2020) as being 0.07, 0.03, 0.04 and 0.09, respectively. Likewise, the heritability of NSC (0.123) was higher than those presented by Salem and Hammoud (2016), Abosaq et al (2017), Sanad and Hassanane (2017), Habib et al (2020) and Zahed et al (2020)(0.006, 0.03, 0.06, 0.04 and 0.01, respectively).…”
Section: Data Presented In Table (contrasting
confidence: 54%
See 2 more Smart Citations
“…Furthermore, Mengistu and Wondimagegn[21], Lehmann et al[46], and Kidane et al[47] reported that DO is the part of the CI, and longer DO reduced the farm profitability. Zahed et al[48] concluded that farm profitability increased by shortening CI, and prolonging this period for 1 day causes a financial loss for the dairy farm. This may be due to the increasing value in milk income.…”
mentioning
confidence: 99%